2023
DOI: 10.1021/acsami.3c05886
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and Pressure Effects on Unrecoverable Voids in Li Metal Solid-State Batteries

Wahid Zaman,
Le Zhao,
Tobias Martin
et al.

Abstract: All-solid-state batteries (ASSB) can potentially achieve high gravimetric and volumetric energy densities (900 Wh/L) if paired with a lithium metal anode and solid electrolyte. However, there is a lack in critical understanding about how to operate lithium metal cells at high capacities and minimize unwanted degradation mechanisms such as dendrites and voids. Herein, we investigate how pressure and temperature influence the formation and annihilation of unrecoverable voids in lithium metal upon stripping. Stac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 47 publications
(81 reference statements)
1
10
0
Order By: Relevance
“…Furthermore, these findings reveal that even a relatively low temperature of 50°C enables the stabilization of the Li/LLZO interface, even when applying the minimum pressure of 1.25 MPa (Figure 3d,f). These results align with the observations made by Hatzell et al, [20] highlighting the substantial impact of temperature in mitigating void formation. It should also be noted that the observed quasi-stable lithium stripping conditions, i.e., a temperature of 50°C and a stack pressure of 1.25 MPa, are within the requirements for practical application in electric vehicles.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Furthermore, these findings reveal that even a relatively low temperature of 50°C enables the stabilization of the Li/LLZO interface, even when applying the minimum pressure of 1.25 MPa (Figure 3d,f). These results align with the observations made by Hatzell et al, [20] highlighting the substantial impact of temperature in mitigating void formation. It should also be noted that the observed quasi-stable lithium stripping conditions, i.e., a temperature of 50°C and a stack pressure of 1.25 MPa, are within the requirements for practical application in electric vehicles.…”
Section: Resultssupporting
confidence: 92%
“…Since void formation during Li stripping is significantly influenced by the external operating conditions, in particular the stack pressure applied to the cell, their effect on the Li/LLZO interface was recently investigated. [19][20][21][22] Namely, Sakamoto et al [19] in his pioneering study aimed to determine the critical stack pressure, which represents the minimum pressure required for electrochemical Li stripping without the occurrence of voids at the Li/LLZO interface. The proposed methodology involved monitoring the overpotential of Li/LLZO/Li symmetrical cells under a constant applied current density (ranging from 0.005 to 0.4 mA cm −2 ) while the stack pressure was gradually reduced from 3.5 MPa to 1 MPa in 0.5 MPa steps.…”
Section: Doi: 101002/admi202300948mentioning
confidence: 99%
See 1 more Smart Citation
“…When 5 MPa of stack pressure is applied at moderate 35 °C to 50 °C, it already facilitates the collapse of pores induced by inhomogeneous stripping with 0.3 mA cm −2 and increases the CCD as discussed recently by Zaman et al. [ 47 ] Furthermore, temperatures above the melting point of lithium can help to negate the issue of pore formation completely, since vacancy diffusion in molten lithium is orders of magnitude faster than in the solid. [ 48 ] A general trend for higher CCD values is expected with increasing temperature and even small temperature differences in the order of 10 K may cause significant changes.…”
Section: Introductionmentioning
confidence: 96%
“…We also note that much of the work in this field uses two-electrode, symmetric cell configurations (i.e., metal/SE/metal configurations, without a reference electrode). Three electrode systems are a known and well used method for cycling investigations in Li-ion research, but we have identified less than a dozen papers on solid state three electrode cycling. ,, Two electrode system interpretations often presume cell polarization is only from the electrode undergoing stripping (where voids are expected), and the plating electrode acts as a stable pseudoreference electrode, but this is often not investigated carefully. Adding a reference electrode, albeit difficult to implement and not without its own limitations, can decouple the interface behaviors in symmetric cells.…”
Section: Introductionmentioning
confidence: 99%